Child Related Leave: Usage and Implications for Gender Equality - Keane, Claire; Alamir, Anouheh; McGinnitty, Frances; O'Shea, Richard; Russell, Helen (ESRI; Irish Human Rights and Equality Commission (IHREC), 2025)
Child-related leave can have important implications for parents and children. Increases in leave duration and benefits reduces the likelihood of parents developing depressive symptoms, have been found to improve maternal and child health, and links have been found between generous maternity leave benefits and reductions in child mortality. Child-related leave policy also has a role to play in the gender income gap, which often starts after the birth of a child. It can protect the employment relationship for mothers and assist them in returning to a job of the same level and pay. It can also allow and encourage greater participation of fathers in caring roles, with research showing that increased leave for fathers results in a more equal division of childcare duties and housework and better father-child relationships. This report focusses on the take-up of child-related leave in Ireland. The leave types analysed are maternity leave (both paid and unpaid), paternity leave and parent’s leave. Maternity leave provides 26 weeks leave covered by Maternity Benefit for the mother post-birth, as well as 16 further weeks unpaid. Paternity leave covers a two-week period in the six months post-birth for the father and is covered by Paternity Benefit. Parent’s leave currently provides each parent with up to nine weeks of leave in the first two years of a child’s life and is covered by Parent’s Benefit. All require the parent to be in employment prior to the birth and to have sufficient social insurance (PRSI) contributions. Paternity leave and parent’s leave are both recent introductions in Ireland (2016 and 2019 respectively), while maternity leave was introduced in Ireland in 1981 (albeit of shorter duration). Using administrative data (a 10 per cent random sample of all births between 2019 and 2022), we estimate that between 2019 and 2022 a little over half of eligible fathers avail of paternity leave. In the two-year period following the introduction of parent’s leave (2020-2021) around one-quarter of eligible fathers and two-thirds of eligible mothers availed of it. Non take-up issues are common internationally. Income-related concerns are often cited as a factor and the flat-rate nature of the payments in Ireland would play a role here, particularly for those on higher incomes not getting an employer top-up. Gendered caring norms and workplace factors also often play a role.